2022
DOI: 10.4193/rhin21.470
|View full text |Cite
|
Sign up to set email alerts
|

The COVANOS trial – insight into post-COVID olfactory dysfunction and the role of smell training

Abstract: Background: Olfactory dysfunction is a cardinal symptom of COVID-19 infection, however, studies assessing long-term olfactory dysfunction are limited and no randomised-controlled trials (RCTs) of early olfactory training have been conducted. Methodology: We conducted a prospective, multi-centre study consisting of baseline psychophysical measurements of smell and taste function. Eligible participants were further recruited into a 12-week RCT of olfactory training versus control (safety information). Patient-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Based on pre-COVID-19 studies, various treatment regimes have been recommended [ 9 , 10 ]: olfactory training [ 11 ], topical administration of vitamin A [ 12 ], omega-3 supplementation [ 13 ], and topical [ 14 ] and systemic corticosteroids [ 15 ]. A positive effect of some of these treatments was possibly recently confirmed for COVID-19-associated smell loss: two studies found a positive effect of olfactory training [ 16 , 17 ]. Hernandez et al showed that omega-3 supplementation improves the olfactory threshold [ 18 ].…”
Section: Introductionmentioning
confidence: 93%
“…Based on pre-COVID-19 studies, various treatment regimes have been recommended [ 9 , 10 ]: olfactory training [ 11 ], topical administration of vitamin A [ 12 ], omega-3 supplementation [ 13 ], and topical [ 14 ] and systemic corticosteroids [ 15 ]. A positive effect of some of these treatments was possibly recently confirmed for COVID-19-associated smell loss: two studies found a positive effect of olfactory training [ 16 , 17 ]. Hernandez et al showed that omega-3 supplementation improves the olfactory threshold [ 18 ].…”
Section: Introductionmentioning
confidence: 93%
“…The strongest evidence for the treatment of COVID‐19 OD recommends olfactory training. 7 , 8 , 9 , 10 , 11 Other proposed therapies based on prepandemic evidence involve the use of topical intranasal medications 12 , 13 , 14 and oral anti‐inflammatory/neuroprotective agents. 15 , 16 , 17 , 18 However, the efficacy remains moderate at best among all current proposed therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…33 Post-Covid long-term anosmi-parosmia (over 1 year) can be seen as a long-term effect of Covid. 34 For the proper management of this condition, the literature needs…”
Section: Konstantinidis Et Al Applied Classical Olfactory Training Fo...mentioning
confidence: 99%